IMPLEMENTASI STRATEGI PEMASARAN ONLINE PRODUK RHTB "KERIPIK SELADA" UNTUK MENINGKATKAN KEPUTUSAN PEMBELIAN DAN MEMAKSIMALKAN KEUNTUNGAN - Lati Sari Dewi; Asep Saeful Falah (JURNAL PENGABDIAN MANDIRI, 2023)
The Community Service Program (PKM) aims to utilize online marketing strategies to increase public awareness of RHTB (Tanjungpura Independent Hydroponics House) products and enhance purchasing decisions, thus maximizing profits. Therefore, the objective of this PKM is to provide the right online strategies to boost sales and maximize profits. In this Community Service Program, there are five stages for the methodology, which include observation, planning, implementation, execution, and evaluation. The results of this PKM indicate that the training program for implementing online marketing strategies for RHTB products in Tasikmalaya is effective as it helps understand how to implement online strategies, influencing purchasing decisions, and maximizing profits.